Sustainability as A Strategy for Fraud Prevention in Universities: A Systematic Review Using PRISMA - Nur Wahyu Ningsih; Einde Evana; Sudrajat (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Academic dishonesty, including plagiarism and data fabrication, remains a persistent challenge in higher education, driven by weak governance, low transparency, and limited stakeholder engagement, yet systematic evidence linking sustainability to fraud prevention is limited. This study aims to analyze how sustainability initiatives in universities mitigate academic misconduct and strengthen governance, transparency, and accountability. Using a Systematic Literature Review (SLR) following PRISMA guidelines, 119 Scopus-indexed articles (2014–2024) were identified, of which 53 met inclusion criteria focusing on sustainability integration in curricula, governance, and campus operations. Thematic analysis revealed that embedding sustainability in academic programs, implementing transparent reporting systems, fostering student and staff participation, and adopting eco-friendly technologies cultivates a culture of integrity, reducing plagiarism and data fabrication by 20–30%. Case studies from Europe, Asia, and Latin America demonstrate that sustainable governance frameworks enhance oversight, ethical behavior, and institutional resilience. These findings suggest that sustainability functions as a comprehensive approach to promoting academic ethics and accountability. By integrating sustainability holistically across operational and academic systems, universities can effectively prevent fraud, reinforce stakeholder responsibility, and contribute to higher education governance literature by providing empirical evidence that links sustainability adoption with improved institutional integrity.